A de novo 10p11.23‐p12.1 deletion recapitulates the phenotype observed in WAC mutations and strengthens the role of WAC in intellectual disability and behavior disorders. Issue 7 (27th April 2016) - Abdelhedi, Fatma; El Khattabi, Laila; Essid, Nouha; Viot, Geraldine; Letessier, Dominique; Lebbar, Aziza; Dupont, Jean‐Michel
Abstract : Chromosomal microarray analysis has become a powerful diagnostic tool in the investigation of patients with intellectual disability leading to the discovery of dosage sensitive genes implicated in the manifestation of various genomic disorders. Interstitial deletions of the short arm of chromosome 10 represent rare genetic abnormalities, especially those encompassing the chromosomal region 10p11‐p12. To date, only 10 postnatal cases with microdeletion of this region have been described, and all patients shared a common phenotype, including intellectual disability, abnormal behavior, distinct dysmorphic features, visual impairment, and cardiac malformations. WAC was suggested to be the main candidate gene for intellectual disability associated with 10 p11‐p12 deletion syndrome. Here, we describe a new case of de novo 10p11.23‐p12.1 microdeletion in a patient with intellectual disability, abnormal behavior, and distinct dysmorphic features. Our observation allows us to redefine the smallest region of overlap among patients reported so far, with a size of 80 Kb and which contains only the WAC gene. These findings strengthen the hypothesis that haploinsufficency of WAC gene might be likely responsible for intellectual disability and behavior disorders. Our data also led us to propose a clinical pathway for patients with this recognizable genetic syndrome depending on the facial dysmorphisms. © 2016 Wiley Periodicals, Inc.